The Role Of CBIA-Based Parent Education In Improving Antimalarial Drug Adherence Among Toddlers In Mimika District - Padallingan, Jenni; Hartayu, Titien Siwi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Malaria remains a significant health challenge in Indonesia, particularly in Mimika District, Central Papua, where high recurrence rates in toddlers are linked to poor adherence to antimalarial drug use. This study aimed to assess whether an educational intervention using the CBIA method could improve parents' knowledge, attitudes, and actions, thereby increasing drug adherence. This quasi-experimental, time-series study involved 62 parents of toddlers with tertian malaria at the Timika Health Center. Participants were divided into an intervention group (30 parents), which received CBIA-based education, and a control group (32 parents). Researchers collected data on parental knowledge, attitudes, and actions at five different time points (pre-education, immediately post-education, 14 days, 2 months, and 3 months post-education) using questionnaires. Drug adherence was measured at two time points (pre-education and 14 days post-education). Statistical analysis involved Wilcoxon and paired t-tests. The CBIA intervention significantly improved antimalarial drug adherence. Post-intervention, parental knowledge surged from 26.7% to 100%, attitudes improved from 3.3% to 73.3%, actions increased from 26.7% to 66.7%, and adherence rose from 46.67% to 73.33%. Statistical tests confirmed significant differences (p 0.01) in knowledge, attitudes, and actions before and after the intervention. The study concludes that the CBIA method is effective in enhancing parents' knowledge, attitudes, and actions, leading to better adherence to antimalarial drug use for toddlers at the Timika Health Center. This approach shows promise for broader implementation in community empowerment programs to boost the success of malaria therapy in children under five.